EARLY ERGONOMIC STRESS IN DENTAL EDUCATION: CHANGES IN PRESSURE PAIN THRESHOLDS, BODY AWARENESS AND MUSCULOSKELETAL DISCOMFORT AMONG PRECLINICAL DENTAL STUDENTS - Fatmagül Varol; Nesime Ayşenur Gülaydın; Sevde Koçyiğit; Pınar Baştürk Merç (Karya Journal of Health Science, 2026)
Objective: Dentistry is widely recognized as an ergonomically challenging profession, with work-related musculoskeletal disorders (WMSDs) often developing early during undergraduate education. While physical workload is heavily studied, how preclinical education affects body awareness and pain sensitivity remains unexamined. This prospective observational study aimed to investigate concurrent changes in self-reported musculoskeletal discomfort, subjective body awareness, and objective pressure pain thresholds (PPT) among third-year dental students during their initial 14-week preclinical training, thereby demonstrating how early ergonomic conditions affect the human body. Method: Thirty-two voluntary, consenting third-year dental students (17 females, 15 males) were prospectively investigated at baseline and at the end of a 14-week preclinical semester. Students with a history of surgery, congenital musculoskeletal anomalies, or chronic diseases were excluded from the study. Subjective parameters were evaluated using the Body Awareness Questionnaire (BAQ) and the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ). Objective tissue hypersensitivity and pain thresholds were mapped via a Baseline® mechanical dolorimeter across validated myofascial trigger points. Statistical significance was set at p